PERSONALIDAD Y RELACIONES SOCIALES EN LOS ESTUDIANTES DE LA UNIDAD EDUCATIVA FERNANDO DAQUILEMA. RIOBAMBA, PERÍODO OCTUBRE 2018 – MARZO 2019. - Cevallos Granizo, Verónica Nataly (2019)
The objective of the research work was to identify personality characters and social relationships; It was carried out in the Educational Unit "Fernando Daquilema" in Riobamba city in the period October 2018 - March 2019, in which the students 'participation of this institution was obtained. The methodology used was not experimental, by the type of research, descriptive, explanatory, correlational, by the field and bibliographic, by the type of cross-sectional study; the population analyzed were the students of the "Fernando Daquilema" Educational Unit; the sample was random non-probabilistic intentional was determined with the students of second and third of baccalaureate; The techniques and instruments used were the 16 PF exam of Cattell and a questionnaire with questions and images, which are specified through a Likert scale, which helped in the interpretation and analysis of the data. A second and a third A Baccalaureate of the "Fernado Daquilema" Educational Unit is in the global dimension of 16 PF in hardness, they are realistic, conservative, dominant people and refer to others with distrust.